2009
DOI: 10.4049/jimmunol.0804135
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene B4 Potentiates CpG Signaling for Enhanced Cytokine Secretion by Human Leukocytes

Abstract: TLRs are known to be important in innate host defense against a variety of microbial infections. In particular, TLR9 has been associated with immune defense against different foreign organisms by recognition of unmethylated DNA sequences. In this report, we provide evidence that leukotriene B4 (LTB4) has the capacity to modulate TLR9 expression on human neutrophils. The effect of LTB4 was found to be specific, because related leukotrienes such as LTC4 and LTD4 or neutrophil agonists IL-8 and C5a failed to modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 57 publications
(97 reference statements)
0
13
0
Order By: Relevance
“…It primes neutrophil responses to toll-like-receptor (TLR) agonists, resulting in enhanced cytokine (IL-8, TNFα) secretion (Gaudreault et al, 2012). TLR9 mRNA levels are upregulated upon priming with LTB 4 , but there is no increase in surface expression of TLR2, TLR4, or the co-receptors TLR1 and TLR6 following LTB 4 exposure (Gaudreault and Gosselin, 2009; Gaudreault et al, 2012). Instead, neutrophil LTB 4 -induced hyper-responsiveness is mediated by the potentiation of TLR-induced intracellular signaling.…”
Section: Phenotypic Changes During Primingmentioning
confidence: 99%
“…It primes neutrophil responses to toll-like-receptor (TLR) agonists, resulting in enhanced cytokine (IL-8, TNFα) secretion (Gaudreault et al, 2012). TLR9 mRNA levels are upregulated upon priming with LTB 4 , but there is no increase in surface expression of TLR2, TLR4, or the co-receptors TLR1 and TLR6 following LTB 4 exposure (Gaudreault and Gosselin, 2009; Gaudreault et al, 2012). Instead, neutrophil LTB 4 -induced hyper-responsiveness is mediated by the potentiation of TLR-induced intracellular signaling.…”
Section: Phenotypic Changes During Primingmentioning
confidence: 99%
“…TLR2 is a cell surface receptor that senses peptidoglycan molecules commonly found on gram-positive bacteria and TLR9 is an endosomal receptor that detects DNA [67, 68]. LTB 4 stimulation upregulates the expression of TLR2 and TLR9 in human neutrophils [69]. Enhanced expression of TLRs could allow for neutrophils to better sense various pathogens and induce a stronger signaling cascade, which allows for a more potent immune response.…”
Section: Effects Of Ltb4 On Host Defense Mechanismsmentioning
confidence: 99%
“…In this regard, it was demonstrated that LTB 4 treatment significantly prevents IAV replication in vivo through an up-regulated production of antimicrobial peptides including beta-defensin–3 and the mouse cathelicidin-related antimicrobial peptide by neutrophils [ 9 ]. In addition, LTB 4 has the capacity to potentiate TLR-mediated response of neutrophils to various TLR agonists [ 10 , 11 ]. Such effects of LTB 4 were relied on at least two mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Such effects of LTB 4 were relied on at least two mechanisms. Firstly, neutrophil treatment with LTB 4 increases expression of intracellular TLR7, 8 and 9, thus enhancing the recognition of foreign RNA and DNA [ 10 , 11 ] and secondly, LTB 4 can also act on key molecules of the TLR signaling cascade, particularly TAK1, to potentiate the secretion of cytokines following recognition of TLR ligands [ 11 ].…”
Section: Introductionmentioning
confidence: 99%